Critique of the Anthropological Foundations of Lifestyle in Adler’s Theory of Individual Psychology from the Perspective of Islam - Amir Qorbanpoor Lafmejani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Lifestyle, which determines a person’s orientation to life, was first introduced in psychology by Alfred Adler. Adler's anthropological perspective, has influenced the formation of the concept of lifestyle. According to Adler, man is a social being whose most important motivation is to overcome inferiority and attain perfection in life, by relying on free will. Also, man is inherently neutral to moral values, and moral values ​​are not real. According to the anthropological view of this theorist and the social and cultural conditions of his life, which is fundamentally different from the Iranian Islamic society, it is necessary to criticize and examine this theory according to the intellectual foundations of Islam. From the Islamic point of view, man is a two-dimensional being whose relation is not limited to the social environment and is also related to himself, God, and nature. Also, the human will is in line with the will of God, and as a result of this will, he is responsible for his behaviors. According to Islam, the purpose of life is to worship and a nearness to God. That is, if all the behaviors of a Muslim man are for God and His pleasure, that is, his intention to do things is only God’s pleasure, he will approach God, and the purpose of his creation will be achieved.